The Californios : a history, 1769-1890 - Janin, Hunt, 1940-; Carlson, Ursula, 1943- (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2017)
"Before the Gold Rush of 1848-1858, Alta (Upper) California was an isolated cattle frontier--and home to a colorful group of Spanish speaking, non-indigenous people known as Californios. Many traces of their culture remain in California. Drawing on firsthand contemporary accounts, the authors chronicle the rise and fall of Californio men and women"--
Introduction: Californios under three flags -- Taking possession of Alta California: the Portolá Expedition -- The Naval Department of San Blas -- Missions and missionaries -- Ranchos -- Presidios and soldiers -- Pueblos and their inhabitants -- A pirate attack on Monterey -- The Old Spanish Trail -- Californio men and Californio women -- Foreigners in Alta California -- Governing the Californios -- Californios in the U.S.-Mexican War of 1846/1848 -- Land titles -- Kaleidoscope of Californio events -- Mariano Guadalupe Vallejo -- The eclipse of the old Californio order: from rancho to barrio -- Opinions on the Californios and their works -- Three young Californio women -- Conclusion: six calamities of Californio life.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Frontier and pioneer life -- California; California -- History -- To 1846.; California -- Ethnic relations; California -- History -- 19th century; Spain -- Colonies -- America -- History; Californie -- Histoire -- Jusqu'à 1846.; Californie -- Histoire -- 19e siècle.; Espagne -- Colonies -- Amérique -- Histoire; HISTORY -- United States -- State & Local -- General; Frontier and pioneer life; Spanish colonies; America; California; To 1899; History